Biological activity of Ruta chalepensis (Rutaceae) and Sechium pittieri (Cucurbitaceae) extracts on Hypsipyla grandella (Lepidoptera: Pyralidae) larvae - Mancebo, Fernando (2001)
Biological activity of a plant extract (common rue, Ruta chalepensis) and a semi purified fraction (from “tacaco cimarrón”, Sechium pittieri) on mahogany shootborer larvae (Hypsipyla grandella) was studied. A randomized complete block design, with four replications, was used. H. grandella third instar larvae were exposed for 24 h to Cedrela odorata leaf discs dipped in several treatment dissolutions of each extract (0.1, 0.32, 1.0, 3.20, and 10%); afterwards, each larva was transferred to a flask containing an artificial diet and was allowed to complete its development. Variables measured included food consumption (foliar area eaten in 24 h), mortality, and developmental effects (developmental time for each larval instar and the pupa, and pupal weight). The common rue extract showed a clear antifeedant activity at a concentration as low as 0.32%, whereas the “tacaco cimarrón” fraction caused toxicity, especially at the two highest concentrations (3.20 and 10%).